PTSD And the Labour Market: Special Problems of Cooperation Between Employers and Employees Suffering from PTSD And Possible Ways of Minimising Risks and Friction in Professional Relations in This Field on The Example of Victims of The Russian-Ukrainian War - Daniil POLIAKOV; Jacek WINIARSKI (Communications of International Proceedings, 2023)
The intention of this study is to study the difficulties and special requirements faced by employees suffering from PTSD or who have increased chances of developing this syndrome, as well as to determine the difficulties faced by employers of such employees. Also, the aim is to develop recommendations for employers to reduce the chances of conflict situations, overtime pressure or failure to meet the necessary conditions for effective and stable cooperation. This study is conducted in the cultural, social and situational context of the Russo-Ukrainian war after the lull period and the subsequent full-scale invasion of 2022. The research design involves the use of a survey method using anonymous questionnaires among able-bodied people affected in one way or another by military operations.
Keywords: Post-traumatic stress disorder (PTSD); War Syndrome